HUBUNGAN SELF-EFFICACY DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS RENDAH - Nurdiana Siregar (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
This study aims to determine whether there is a significant relationship between students' mathematical self-efficacy and student learning outcomes in elementary grades. The research method used is descriptive method with the correlation approach. The instrument used for both variables is a scale of self-efficacy to see students' mathematical self-efficacy and student learning outcomes from the Final Examination (UAS). The self-efficacy scale contains 20 statements containing four alternative answers. The population of this study were all elementary school students, namely 156 students with a sample of 63 students. Data were analyzed with Pearson followed by t-test, previously obtained that the data of self-efficacy and mathematics learning outcomes were normally distributed and linear. Data on self-efficacy is 0.173> 0.05 and data on student mathematics learning outcomes is 0.2> 0.05. Linearity was fulfilled at 0.04 <0.05. Obtained tcount = 2,9255 while ttable = 1,9996, so tcount> ttable means that Ho is rejected. It can be stated that there is a significant relationship between self-efficacy and mathematics learning outcomes of elementary school low grade students.